Antral mucosal perfusion is not increased in GAVE. Issue 3 (3rd April 2017) - Tekola, Bezawit; Smith, Elliot; Mann, James; Patrie, James; Moskaluk, Christopher; Caldwell, Stephen
ABSTRACT: Objectives : Although a common cause of intestinal blood loss, the pathophysiology of gastric antral vascular ectasia (GAVE) is not well understood. We aimed to evaluate gastric antral and body mucosal flow in GAVE patients compared to a control population using laser Doppler flowmetry. Methods : 27 patients with GAVE and 11 control patients without GAVE were evaluated using an endoscopic LDF probe. The probe was placed in the gastric antrum and body in order to calculate standardized mucosal flow rates recorded as perfusion units (PU). Results : Despite its hyperemic appearance and propensity to bleed, antral blood flow was not increased in GAVE: 115.5 PU (IQR: [94.4, 135.9 PU]) in GAVE versus 123.7 PU (IQR: [109.7, 186.5 PU]) in controls. There was a significant gradient between the gastric body and antral blood flow in GAVE (p < 0.001) that was not evident in controls. Conclusion : These results indicate that antral mucosal blood flow is not increased in GAVE despite its grossly hyperemic appearance. A mild but statistically significant gradient was noted between the gastric antrum and body in patients with GAVE compared to controls. The pathophysiological significance of this finding is uncertain.